Generic Synopsis of the Formicidae of Vietnam (Insecta: Hymenoptera), Part II—Cerapachyinae, Aenictinae, Dorylinae, Leptanillinae, Amblyoponinae, Ponerinae, Ectatomminae and Proceratiinae - Eguchi, Katsuyuki; Viet, Bui Tuan; Yamane, Seiki (Zootaxa, 2014)
Of the subfamilies and genera known from Vietnam, the following taxa are treated in this second part of the series entitled “Generic Synopsis of the Formicidae of Vietnam”: Cerapachyinae: Cerapachys, Simopone; Aenictinae: Aenictus; Dorylinae: Dorylus; Leptanillinae: Leptanilla, Protanilla; Amblyoponinae: Myopopone, Mystrium, Opamyrma, Prionopelta, Stigmatomma; Ponerinae: Anochetus, Brachyponera, Buniapone, Centromyrmex, Cryptopone, Diacamma, Ectomomyrmex, Euponera, Harpegnathos, Hypoponera, Leptogenys, Mesoponera, Odontomachus, Odontoponera, Parvaponera, Platythyrea, Ponera, Pseudoneoponera; Ectatomminae: Gnamptogenys; Proceratiinae: Discothyrea, Probolomyrmex, Proceratium. For each of these subfamilies we provide keys to genera (when there is more than one genus) known from Vietnam. For each genus we provide a synopsis and a list of Vietnamese species.